Ethical Challenges and Countermeasures in Computer Science Development under Artificial Intelligence - Lei, Tang (International Journal of Computer Science and Information Technology, 2025)
As artificial intelligence technology deeply permeates the field of computer science, the discipline is undergoing a paradigm shift from instrumental rationality to value-based rationality. AI-driven algorithmic innovation, data utilisation, and autonomous decision-making systems have not only restructured the developmental logic of computer technology but also precipitated unprecedented ethical crises. This paper systematically analyses the ethical dilemmas confronting computer science and technology within the AI context across data governance, algorithmic application, technological power distribution, and global governance. Drawing upon representative case studies and international practices, it proposes pragmatic yet forward-looking countermeasures across four dimensions: legal regulation, technological reconfiguration, multi-stakeholder collaboration, and global governance. This framework provides theoretical underpinnings and practical pathways for advancing the sustainable development of computer science and technology within an ethical framework.